THE EFFECT OF PHONETIC TRAINING ON THE PERCEPTION OF ENGLISH VOWELS (Journal of Contemporary Philology, 2024)
This study aims to explore the effect of phonetic training on the perception of English vowels /iː, ɪ, e, æ/ by Macedonian learners of English. The training is perceptual and combines traditional and communicative-cognitive pronunciation teaching techniques focusing on raising learners’ awareness by exposing them to authentic speech and not requiring them to practice pronunciation. Sixty-two participants were divided into two groups: experimental (n= 31) and control (n= 31). Only the participants in the experimental group received the perceptual training. All participants completed four tests for vowel identification: one pre-test, one post-test and two generalisation tests. The data were analysed for the effect of training on participants’ vowel perception. The results show indicative improvement of the perception of the tested phenetic contrasts, suggesting that the learners’ L2 phonological system is still unstable and developing.
Keywords: perceptual training; vowel discrimination and identification; critical listening; corrective feedback; communicative exercises